THE PLACE AND IMPORTANCE OF THE MEDIA SPACE IN THE RELATIONSHIP BETWEEN THE INDIVIDUAL AND SOCIETY - Khaydarova Dilorom Abdukhamidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the issue that the media space is a separate reality, completely unthinkable, being a physical component of the media, constituting ideological schemes and models of actions of subjects consuming and producing information using methods and means of mass communication. maybe culturologists, psychologists, political scientists, journalists and sociologists.